2003
DOI: 10.4315/0362-028x-66.9.1550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter within a Swine Slaughter and Processing Facility

Abstract: In this work, the occurrence of Campylobacter in a swine slaughter and processing facility was studied. Thirty composite carcass samples, representing 360 swine carcasses, were taken immediately after exsanguination, immediately after polishing, after the final wash, and after overnight chilling at 2 degrees C. Thirty matching composite rectal samples were also taken immediately after exsanguination, and 60 nonmatching individual colon samples were collected from the same lot of swine during evisceration. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 30 publications
5
33
2
Order By: Relevance
“…C. coli was the most common species isolated from pigs. This is consistent with the findings of most investigations of the carriage of campylobacters in swine (53,63,69,75). Nevertheless, there are also reports of a high prevalence of C. jejuni in pigs (32,91).…”
Section: Discussionsupporting
confidence: 81%
“…C. coli was the most common species isolated from pigs. This is consistent with the findings of most investigations of the carriage of campylobacters in swine (53,63,69,75). Nevertheless, there are also reports of a high prevalence of C. jejuni in pigs (32,91).…”
Section: Discussionsupporting
confidence: 81%
“…Despite the high rate of Campylobacter spp. isolation from the intestine contents reaching 53.9% in cattle (Nesbakken et al 2003) and up to 100% in swine (Pearce et al 2003), the level of contamination of bovine and swine carcasses stands at a much lower level. Wieczorek and Osek (2010) confirmed the presence of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 98%
“…The rapid and sensitive detection of C. jejuni is necessary for the maintenance of a safe food/water supply in China and the real-time PCR assay provides a specific, sensitive and rapid method for quantitative detection of C. jejuni. Pearce et al [124] reported that although Campylobacter is highly prevalent in the intestinal tracts of swine arriving at the slaughter facility, this microorganism does not progress through the slaughtering operation and is not detectable on carcasses after overnight chilling. Sharma et al [152] critically examined the potential of emerging water-borne pathogens in both developed and developing nations and the global epidemiology of a number of cases involving hepatitis viruses (including hepatitis E virus), Campylobacter jejuni, microsporidia, cyclospora, Yersinia enterocolitica, calciviruses and environmental bacteria like Mycobacterium spp., Aeromonads, Legionella pneumophila and multidrug-resistant Pseudomonas aeruginosa that have been associated with water-borne illnesses.…”
Section: Food Related Environmentsmentioning
confidence: 99%